„Zwierzę w Belwederze” – narodziny warszawskiego mitu o Wielkim Księciu Konstantym - Wesołowska, Aleksandra (Studia z Historii Społeczno-Gospodarczej XIX i XX Wieku, 2012)
Constantine Pawlowicz Romanow is a character, which had infamously enrolled on cards of history. Thanks to nineteenth-century diarists, we know why he deserved on this opinion. Other people saw his behavior as very exotic and those situations resulted in stories about savage man living in a Belvedere Palace. Consecutive years brought another, very extension stories about Russian Tsar`s son, which released imagine for next generations, allowing for growing the legend of “wild animal Constantine” – man, who persecuted inhabitants of capital. To look carefully, how myth about Grand Duke was born and prevailed, we have to know about historical developments in nineteenth-century Warsaw. Trying to describe daily life in Warsaw, slowly pushing people to revolution, I have noticed that everybody had seen Constantine like main protagonist of this situation. His “foreignness” and “russianness” were the main reasons for provocateurs calling for actions against Russian Empire. For Poles, Constantine was like Russian Empire in Warsaw. Prince, as a representative of this empire, became the mortal enemy. Prince did not take into account polish elite. He considered himself as a simple tributary of his brothers, but he liked using his position. Nobody understood his aggression in one moment and big happiness in the next. He liked power, which he recognized living in the Polish Kingdom. The November Uprising deprived him everything and drove abroad. His senses came too late. Constantine refused to send his troops against the revolutionaries, saying: “The Poles have started this disturbance, and it’s Poles that must stop it”, and left the suppression of the revolt in the hands of the Polish government. He himself retreated behind Russian lines but following the failure of the uprising expressed admiration for the valor of the Polish insurgents.